PELAYANAN KESEHATAN REPRODUKSI REMAJA DI PUSKESMAS: ISU DAN TANTANGAN - Augustina Situmorang (Jurnal Kependudukan Indonesia, 2011)
In line with the International Conference on Population and Development (ICPD) in 1994 in Cairo, 2001, The Indonesian Ministry of Health developed an integrated essential reproductive health Services at primary health care which include Adolescence Reproductive Health services (ARH). Utilized qualitative approach, this article examine the implementation of ARH in 16 primary health care (puskesmas) which are located in four districts/city namely Pontianak City, Landak District, Ogan Komering Ilir District and Tasikmalaya District. The study results showed that ARH programs have not been folly implemented. This is due to several obstacles including (a) The limited knowledge of health personnel in the puskesmas, (b) Obstacles related to legal and policy aspects; (c) Obstacles related to socio-cultural aspects. Considering the increase number of adolescents who have engaged in risky sexual activities, it is important to develop comprehensive approaches to this phenomenon, especially at puskesmas. To do so, the national consensus on the right of adolescents to obtain comprehensive information and services related to sexual and reproductive health is urgently needed The consensus of course has to consider the religious and cultural norm, but it also has to accept the real condition of today s adolescents.